Biometria e processamento dos frutos da macaúba (Acrocomia ssp) para a produção de óleos - Teddy Marques Farias (2010)
The world has experienced fast and major transformations in their economic, social, scientific and technological structures. These changes come with a reflection about human behavior in relation to the Earth Planet and with himself. At the twentieth century the imperative system of production and consumption resulted in several problems that profoundly affected the relationship between people and the environment, reaching a point near of the unsustainable, endangering the political-social system and life on the planet. Brazil, holder of the highest biodiversity in the world, has been pressured to provide solutions for the preservation of its natural resources. But the solution to the problems existing here are not simple. The equations needed to solve such issues are complex and have "n" variables, given the size and heterogeneity of the country's problems to be solved. Moreover, the current preservation systems have been based on North America models and therefore are not suitable for Brazilian conditions, which mean that we need to formulate a specific method in order solve environmental issues in Brazil. This study aimed at assessing the oil potential of macaúba, a native palm (Acrocomia) of wide distribution in various regions of the country and Latin America, with a production potential of up to 6000kg of oil / ha. The macaúba is used by local traditional populations for artisanal or semi-industrials purposes: the quantity and quality of the extracted oils has attracted the interest of various industry segments such as food industry, cosmetics and biofuels and others. However, obtaining the oils of the fruits of this palm with a good quality still faces some difficulty inherent in the nature of raw material. The main problem presented is the rapid development of acidity in the oil of the fruit pulp, caused by infestation of microorganisms from the macaubais environment, which increase rapidly the level of acidity of the oil out of the standards required by various branches of industry. The accomplished experiments of this study had primarily an exploratory nature, including the following aspects: (i) the characterization of the fruits collected from Macaubas of three distinct regions, in order to evaluating the variables of fruit quality and its representativeness in relation to oil content of fruit; (ii) the storability characteristics of the fruit by observing the dynamics of the development of free acidity, as well as its associated factors, in order to propose an appropriated sanitation methods; (iii) the evaluation of the mechanical pressing process for oil extraction, pulp oil and kernel oil, by analyzing the oils quality and the mass balance of the process; (iv) discussion about the extactivism of macauba in the north of Minas Gerais. The results confirm the quality and the high oil potential from fruits of natives Macauba palm tree.